Optimization of thermal annealing of zinc oxide films for enhancing performances of near-infrared organic photodetectors - Son, Ji Yeon; Eun, Hyeong Ju; Seo, Gyeong Uk; Lee, Ah Young; Kim, Ju Hyung; Kim, Jong H. (Dyes and Pigments, 2023)
In this paper, we report the effect of annealing time of hole-blocking ZnO layers prepared by a sol-gel process on the performance of near-infrared organic photodetectors (NIR-OPDs). We investigated changes in the dark current density (JD) values of NIR-OPDs depending on the different annealing time of 10, 20, 30, and 60 min. From the devices based on 20 min-annealed ZnO layers, we attained the lowest JD of 1.10 × 10−8 A/cm2 and the highest specific detectivity (D*) of 6.90 × 1012 Jones in response to 850 nm NIR light. Morphology characterization using atomic force microscopy (AFM) revealed that the 20 min annealed ZnO layer demonstrated the lowest surface rms roughness. The lowest series resistance (RS) and the highest shunt resistance (RSH) obtained from the 20 min annealed ZnO film provided evidence of the improved interface between ZnO and photoactive layers, which enabled the efficient suppression of JD and optimized D* values. Our results suggest that the control of annealing time for ZnO film can be a simple and effective strategy to enhance the performance of various types of OPDs based on ZnO layers.
Keywords: Annealing time; D values; Near Infrared; Near infrared organic photodetector; Near-infrared; Organics; Performance; Specific detectivity; ZnO films; ZnO layers; Annealing time; Near infrared organic photodetector; Specific detectivity; Surface roughness; Zinc oxide